Design, synthesis and evaluation of lactoside-derived galectin-3 inhibitors. Issue 3 (24th March 2019) - He, Peng; Zhao, Chuanfang; Sun, Xue; Du, Yuguo
Abstract: Based on docking computation, a panel of lactoside derivatives have been designed as galectin-3 inhibitors. Suitable functional group modifications at C′-3 of methyl lactoside were predicted to supply some additional π–cation, π…H–O, and hydrogen bond interactions between the designed substrates and galectin-3 residues. The selected compounds, giving higher TotalScore in docking calculations, were thus synthesized, and their binding affinities toward galectin-3 were evaluated with SPR assay.